Evaluation of corrosive environment impact on low cost Fe/Al ADDED SAC105 solder alloys / Nor Ilyana Muhd Nordin - Nor Ilyana, Muhd Nordin (2017)
The current trend for multi-functioning miniaturised devices has driven research and development of higher density electronics. This has a significant impact on electronics packaging, especially in solder joints with reduction in solder contact area. This current trend has placed a challenge in ensuring the reliability of the soldered joint. Concerns on solder joint reliability in terms of its mechanical, electrical, and corrosion behaviour is critical to the operation of the overall electronic device. This work studies the lead-free solder formulation, Fe/Al added Sn-1.0Ag-0.5Cu (SAC105) solder alloy, in terms of solder joint integrity exposed to the corrosive environment. Test specimens of printed circuit board (PCB) solder board mounted with solder balls of the mentioned formulations were fabricated. Simulation of corrosive environment using salt mist. A solder ball shear test was performed to observe joint strength (solder/substrate interface). Potentiodynamic polarization was conducted to provide an electrochemical understanding of the corrosion mechanism for these solder alloys in a salt solution. With addition of Al, material experience better passivation that increase the corrosion resistance. The corrosion resistance of Al-added was found better than SAC105, whilst the Fe added solder was comparable to SAC105. It is interesting to note that for Fe-added SAC 105, formation of passivation layer provides resistance towards aqueous environment, which is beneficial as Fe was initially thought to be susceptible to corrosion. Microstructural study and element mapping were carried out to complement the analysis of the potentiodynamic and shear stress studies, especially in correlating the role of intermetallic compounds (IMCs) to mechanical performance. The minor alloying addition of Fe or Al in SAC105 solder formed intermetallic compounds (IMC) FeSn2 for Fe-addition, and Al-Cu and Al-Ag for Al addition. The presence of these IMCs have significant impact on mechanical properties after exposure to an aqueous environment. These IMCs, although chemically inert, impose a potential difference between the elements within the alloy and encourage dissolution which results in modification of the mechanical and surface properties. The ball shear test performed has indicated that the addition of Fe/Al to the SAC105 alloy results in preservation of the joint strength despite excessive exposure to the corrosive environment. Specimens containing solder balls of Fe/Al added SAC105 have shown to perform similar to SAC105. The addition of Al has altered the material surface with a more densely-packed corrosion product which hinders the creation of crevices on the surface that may encourage further corrosion. On the other hand, for the case of Fe-added SAC solder, the presence of FeSn2 IMC through Fe addition created a more noble microstructure within the SAC105 alloy. Finite element analysis (FEA) simulates the impact of solder ball size on the shear strength of the solder/substrate joint. Conclusively, the evaluation of solder joints of Fe or Al added SAC 105 have shown good mechanical improvement and enhanced corrosion resistance over SAC 105. This demonstrates an improvement of the SAC105 solder formulation by using cost-effective and commonly available additions such as Fe and Al.